2020
DOI: 10.3390/cancers12113391
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake in Association with All-Cause Mortality and Colorectal Cancer Mortality among Colorectal Cancer Survivors: A Systematic Review and Meta-Analysis of Prospective Studies

Abstract: We carried out a systematic review and meta-analysis to determine the effects of both prediagnostic and postdiagnostic dietary intake on all-cause mortality and CRC-specific mortality among CRC survivors. An extensive search of PubMed and Embase was conducted to identify eligible studies. We applied a random-effects model to estimate the pooled relative risks (RRs)/hazard ratios (HRs) and their 95% confidence intervals (CIs). As a result, a total of 45 studies were included in the final analysis. Pooled effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 87 publications
1
19
0
Order By: Relevance
“…The observed threshold effect is biologically plausible because dietary fiber, particularly soluble fiber, has limits in transport, metabolism, or storage, and their beneficial effects may be mediated by intestinal bacteria through fermentation that can be saturated. In a meta-analysis of dietary intake and CRC survival published in 2020, Hoang et al [ 16 ] reported that fiber consumption was not related to either all-cause (HR: 0.84, 95% CI: 0.58–1.22) or CRC-specific mortality (HR: 0.72, 95% CI: 0.44–1.18). Hoang’s findings are apparently inconsistent with ours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed threshold effect is biologically plausible because dietary fiber, particularly soluble fiber, has limits in transport, metabolism, or storage, and their beneficial effects may be mediated by intestinal bacteria through fermentation that can be saturated. In a meta-analysis of dietary intake and CRC survival published in 2020, Hoang et al [ 16 ] reported that fiber consumption was not related to either all-cause (HR: 0.84, 95% CI: 0.58–1.22) or CRC-specific mortality (HR: 0.72, 95% CI: 0.44–1.18). Hoang’s findings are apparently inconsistent with ours.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, immortal time bias may influence the results, but this is minimized by using family proxies to enroll deceased cancer patients. Last, as a limitation shared by all meta-analyses on published articles, the cut-off level of dietary intake quantiles was generally inconsistent across studies; we may, therefore, have overestimated or underestimated the effects of fiber on CRC survival [ 16 ]. The between-study heterogeneity in our study may be attributed to the methodological or actual differences across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid rise in CRC incidence was associated with urbanisation and lifestyle westernisation, which caused a change in eating behaviour [ 2 ] that increased obesity prevalence [ 3 , 4 , 5 ]. Furthermore, dietary factors significantly contributed to CRC mortality risk [ 6 ]. Nevertheless, CRC is highly preventable [ 7 ]; therefore, an important CRC prevention measure is to improve the modifiable CRC risk factors in diet and nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that a high intake of dietary carbohydrates may be associated with the increased risk of many health outcomes, such as all-cause mortality rate and many cancers such as CRC (13,14). A high glycemic load (GL) diet such as the western diet which includes high amounts of refined carbohydrates (for example white rice and noodles) may promote CRC risk through its hyperinsulinemia effects (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%